Ionospheric Precursors to Earthquakes: A Review of Mechanisms and Observations - Prasert Kenpankho (IntechOpen eBooks, 2026)
This chapter delves into the dynamic interplay between seismic phenomena and ionospheric variability through the lens of lithosphere–atmosphere–ionosphere coupling (LAIC). By integrating GNSS-based observations and advanced ionospheric modeling, it investigates how total electron content (TEC) anomalies may serve as electromagnetic fingerprints of impending earthquakes. The study focuses on Thailand during Solar Cycle 24 (2007–2020), utilizing multisource TEC datasets, including GPS, IGS, and IRI, to detect preseismic ionospheric disturbances. Statistical correlation analyses reveal that TEC anomalies are more pronounced prior to high-magnitude earthquakes (Mw ≥5.0), suggesting a viable pathway for early warning systems. The chapter also examines the confounding effects of geomagnetic storms and solar activity, emphasizing the need for space weather calibration in seismo-ionospheric studies. By bridging geophysics and space science, this work contributes to the emerging field of earthquake forecasting via ionospheric diagnostics.
Keywords: Earthquake Detection and Analysis; Ionosphere and magnetosphere dynamics; Geomagnetism and Paleomagnetism Studies